2021
DOI: 10.1002/saj2.20227
|View full text |Cite
|
Sign up to set email alerts
|

Biochar amendment did not influence the growth of two tree plantations on nutrient‐depleted Ultisols in the south Ecuadorian Amazon region

Abstract: The literature suggests that biochar increases the fertility of degraded, nutrient-poor tropical soils. We hypothesized that the addition of biochar (a) increases tree growth in two plantations on Ultisols in the south Ecuadorian Amazon region, (b) reduces litterfall during the dry season because the soil remains moister, and (c) improves the benefit-cost ratio of the plantation. We grew two tree species-the native leguminous Schizolobium parahyba var. amazonicum (Ducke) Barneby and the exotic Gmelina arborea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 79 publications
5
26
0
1
Order By: Relevance
“…N. Xu et al (2016) attributed this increase in part to reduced N leaching losses because of the improved N retention after amendment of biochar. However, the increase in total N concentrations in topsoil at our two study sites did not result in improved growth in the treatments with only biochar but no mineral fertilizer plus lime (Gonzalez Sarango et al, 2021). Most of the additional N must have been stored in nonbioavailable forms, which is in line with the finding that the Olsen-NH 4 + -N concentration did not respond significantly to the biochar amendment (Supplemental Table S2).…”
Section: Effect Of Biochar On Nutrient and Na Concentrationssupporting
confidence: 82%
See 4 more Smart Citations
“…N. Xu et al (2016) attributed this increase in part to reduced N leaching losses because of the improved N retention after amendment of biochar. However, the increase in total N concentrations in topsoil at our two study sites did not result in improved growth in the treatments with only biochar but no mineral fertilizer plus lime (Gonzalez Sarango et al, 2021). Most of the additional N must have been stored in nonbioavailable forms, which is in line with the finding that the Olsen-NH 4 + -N concentration did not respond significantly to the biochar amendment (Supplemental Table S2).…”
Section: Effect Of Biochar On Nutrient and Na Concentrationssupporting
confidence: 82%
“…This short-term increase might have been sufficient to precipitate Fe(OH) 3 , which then is not easily redissolved. Although the biochar amendment did increase the pH values, particularly at La Victoria (Gonzalez Sarango et al, 2021), the effect was less pronounced, and we suspect that the soil solution pH values did not change similarly strongly as in response to liming. As a consequence, our biochar amendment did not have a significant effect on the Fe availability in the topsoil, which is similar to findings of Abedin and Unc (2020) who reported that an amendment of 15 t ha −1 biochar did not significantly change Fe availability in the topsoil.…”
Section: Effect Of Biochar On Nutrient and Na Concentrationsmentioning
confidence: 82%
See 3 more Smart Citations